2018
DOI: 10.1089/tmj.2017.0075
|View full text |Cite
|
Sign up to set email alerts
|

Usability, Acceptability, and Impact of a Pediatric Teledermatology Mobile Health Application

Abstract: A mobile health app allowing families to directly consult a pediatric dermatologist was usable, acceptable, and expedited care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Additionally, the lack of in-person contact restricted dialog between patients and dermatologists, and created communication difficulties for providing patients with diagnoses, advice, and emotional support [ 43 44 , 55 , 57 ]. Studies also reported several technological limitations associated with teledermatology; these include slow image uploading and downloading speed [ 36 , 43 ] and cumbersome technology user interface [ 37 , 38 , 46 , 48 , 57 , 59 ]. Primary care providers reported additional barriers related to the time and money required to set up teledermatology technology [ 39 , 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the lack of in-person contact restricted dialog between patients and dermatologists, and created communication difficulties for providing patients with diagnoses, advice, and emotional support [ 43 44 , 55 , 57 ]. Studies also reported several technological limitations associated with teledermatology; these include slow image uploading and downloading speed [ 36 , 43 ] and cumbersome technology user interface [ 37 , 38 , 46 , 48 , 57 , 59 ]. Primary care providers reported additional barriers related to the time and money required to set up teledermatology technology [ 39 , 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Questionnaires (20 studies, 67% of included studies) and interviews (9 studies, 30% of included studies) were the most common methods of data collection. Only three of the thirty studies used a theoretical implementation framework to guide their investigation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Each of the three studies used the technology acceptance model, a model designed to assess individuals' level of acceptance of technology (i.e., teledermatology).…”
Section: Theory/framework Usementioning
confidence: 99%
See 1 more Smart Citation
“…For those 13 studies, scores of agree (4) and strongly agree (5) generally were deemed satisfactory [10-14, 22, 26-32]. Three studies scored statements of satisfaction on an agree/disagree basis [18][19][20]. The survey characteristics (whether a five-point grading scale was used, the method of administration, and acceptable scores) are set out in Table 2.…”
Section: Study Survey Methodsmentioning
confidence: 99%
“…9,10 Others have used telemedicine and e-consult systems to provide more timely dermatologic care to patients. [11][12][13] Again, these systems have generally been well-received by both patients and PCPs. However, there continue to be challenges around reimbursement, technology and legal liability.…”
Section: Introductionmentioning
confidence: 99%